2013
DOI: 10.1007/s00405-013-2810-8
|View full text |Cite
|
Sign up to set email alerts
|

Brain voice processing with bilateral cochlear implants: a positron emission tomography study

Abstract: Most cochlear implantations are unilateral. To explore the benefits of a binaural cochlear implant, we used water-labelled oxygen-15 positron emission tomography. Relative cerebral blood flow was measured in a binaural implant group (n = 11), while the subjects were passively listening to human voice sounds, environmental sounds non-voice or silence. Binaural auditory stimulation in the cochlear implant group bilaterally activated the temporal voice areas, whereas monaural cochlear implant stimulation only act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…This is plausible due to the fact that the sentences used in our discrimination paradigm were syntactically simple and their processing may have relied rather on the ventral than the dorsal pathways. Regarding the parietal areas, the lack of activation in these regions might be related to the fact that participants were stimulated unilaterally, while previous studies reporting parietal recruitment during speech processing are restricted to CI users with bilateral stimulation (Coez et al, 2014). However, our CI users showed supplementary activation in the hippocampus (BA 48), pointing to memory functions involved in performing the semantic-anomaly paradigm.…”
Section: Brain Regions Recruited For Speech Processing In Nh Listenermentioning
confidence: 50%
See 1 more Smart Citation
“…This is plausible due to the fact that the sentences used in our discrimination paradigm were syntactically simple and their processing may have relied rather on the ventral than the dorsal pathways. Regarding the parietal areas, the lack of activation in these regions might be related to the fact that participants were stimulated unilaterally, while previous studies reporting parietal recruitment during speech processing are restricted to CI users with bilateral stimulation (Coez et al, 2014). However, our CI users showed supplementary activation in the hippocampus (BA 48), pointing to memory functions involved in performing the semantic-anomaly paradigm.…”
Section: Brain Regions Recruited For Speech Processing In Nh Listenermentioning
confidence: 50%
“…We also expected differences in cortical activation in the (pre)frontal, the superior temporal, and the posterior middle temporal regions, i.e., in temporo-frontal networks, between CI users with higher and lower speech recognition ability (Friederici, 2012). In addition, we expect that CI users with higher speech comprehension have stronger activation in regions and networks representing cognitive functions, such as the temporal cortex (memory) and parietal cortex (attention) (Coez et al, 2014). Finally, we tested the hypothesis that cross-modal (i.e., auditory) activation of the occipital (i.e., visual) cortex is beneficial in terms of speech understanding with a CI (Giraud et al, 2001b).…”
Section: Introductionmentioning
confidence: 98%
“…De Seta et al 27 showed that speech performance of the poorer ear continues to improve between 1 and 5 years after bilateral simultaneous implantation, whereas such an improvement is not observed after 1 year in unilateral implantation. One possible explanation could be related to the benefit of long-term increased stimulation of cortical auditory areas in bilaterally implanted patients 28 29 . Nonetheless, we cannot ignore that there may be a sampling bias as our bilaterally implanted candidates were usually selected from good unilateral performers.…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral implantation recruited more equally auditory cortices in both hemispheres [7]. Finally, binaural vs. monaural discrimination of voice vs. non-voice stimuli revealed, that binaural implant stimulation is associated with activation in right fronto-parietal networks contributing to improved task performance [8].…”
Section: Plasticity After Cochlear Implantationmentioning
confidence: 86%